TEACHING ONLINE IN PANDEMIC TIME:THE EXPERIENCE OF INDONESIAN EFL TEACHERS - Aji Budi Rinekso; Ahmad Bukhori Muslim; Okta Lesagia (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Myriad studies reported abrupt transition of face-to-face classrooms to online learning due to pandemic and the results were various, contextually-bounded from country to another. Yet, studies exploring the aforementioned issue in Indonesian EFL context are still scarce. This study explores issues and challenges experienced by Indonesian EFL teachers in conducting English online learning during the pandemic within qualitative approach. Twenty-five secondary English teachers from urban, suburban, rural and remote area participated in this study. Subsequently, online questionnaire and semi-structured virtual interviews were employed to collect data. Then, the data were analyzed descriptively and thematically. The results showed that the participants had positive responses to online learning to maintain learning processes in pandemic time. In terms of teaching language skills, the participants argued that speaking is the most challenging to teach online. Moreover, the study identified three types of online learning challenges related to technical aspects, teachers and students. Pedagogically, this study implied that pandemic time has given teachers disguised blessings as they had an opportunity to upgrade their information technology skills and literacies.